THE DEVELOPING OF LEARNING MEDIA BASED ARTICULATE STUDIO’13 IN ASSESSMENT COURSE AT BIOLOGY EDUCATION STUDY PROGRAM - Hepta Bungsu Agung Jayawardana; Mochammad Maulana Trianggono (JURNAL PENA SAINS, 2018)
The purpose of the study is developing articulate studio '13 based learning expert validation through the media and examine the effect on the student learning outcomes. The participants include 48 students of biology education IKIP PGRI Jember with One Shot-Case Study design. The data is analyzed descriptively qualitative. The result of the validation is categorized, the feasible learning activity is good, the student's response is well classified and learning outcomes is complete. The conclusion of this study is learning media based articulate studio '13 can improve student motivation and learning outcomes.